Nucleic Acid Drugs - Murakami, Akira; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
New Antisense Strategies: Chemical Synthesis of RNA Oligomers, by Junichi Yano und Gerald E. Smyth Development and Modification of Decoy Oligodeoxynucleotides for Clinical Application, by Mariana Kiomy Osako, Hironori Nakagami und Ryuichi Morishita Modulation of Endosomal Toll-Like Receptor-Mediated Immune Responses by Synthetic Oligonucleotides, by Ekambar R. Kandimalla und Sudhir Agrawal Delivery of Nucleic Acid Drugs, by Yan Lee und Kazunori Kataoka Aptamer: Biology to Applications, by Yoshikazu Nakamura Development and Clinical Applications of Nucleic Acid Therapeutics, by Veenu Aishwarya, Anna Kalota und Alan M. Gewirtz.
New Antisense Strategies: Chemical Synthesis of RNA Oligomers, by Junichi Yano und Gerald E. Smyth Development and Modification of Decoy Oligodeoxynucleotides for Clinical Application, by Mariana Kiomy Osako, Hironori Nakagami und Ryuichi Morishita -- Modulation of Endosomal Toll-Like Receptor-Mediated Immune Responses by Synthetic Oligonucleotides, by Ekambar R. Kandimalla und Sudhir Agrawal -- Delivery of Nucleic Acid Drugs, by Yan Lee und Kazunori Kataoka -- Aptamer: Biology to Applications, by Yoshikazu Nakamura -- Development and Clinical Applications of Nucleic Acid Therapeutics, by Veenu Aishwarya, Anna Kalota und Alan M. Gewirtz.
Keywords: Polymers .; Medicinal chemistry; Pharmacy; Biochemistry; Electrochemistry; Polymer Sciences; Medicinal Chemistry; Pharmacy; Biochemistry, general; Electrochemistry